1976
DOI: 10.1007/bf00454850
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and degradation of lindane by soil microorganisms

Abstract: Of 147 microorganisms isolated from a loamy sand, 71 showed good growth with lindane (gamma-1,2,3,4,5,6-hexachlorocyclohexane) and produced chloride in an aqueous medium. Thirteen soil microorganisms were selected to study the utilization of lindane. Lindane was metabolized by the microbes to gamma-2,3,4,5,6-pentachloro-1-cyclohexene (gamma-PCCH), alpha-3,4,5,6-tetrachloro-1-cyclohexene (alpha-TCCH), beta3,4,5,6-tetrachloro-1-cyclohexene (beta-TCCH), gamma-3,4,5,6-tetrachloro-1-cyclohexene (gamma-TCCH), and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 13 publications
1
46
0
Order By: Relevance
“…Also, there is evidence that several bacteria and fungi isolated from soil could convert y-HCH to y-2, 3,4,5,4,5,, and pentachlorobenzene (PCB) (Tu 1976). One of the cultures, Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is evidence that several bacteria and fungi isolated from soil could convert y-HCH to y-2, 3,4,5,4,5,, and pentachlorobenzene (PCB) (Tu 1976). One of the cultures, Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…This study indicates that some g-HCH metabolites produced by A. citreus BI-100 identified are quite different from those produced from g-HCH by any other single microorganism reported in the literature (Benezet and Matsumura, 1973;Francis et al, 1975;Matsumura et al, 1976;Nagata et al, 1993;Tu, 1976;Yule et al, 1967). The spent culture of g-HCH at 72 h showed an absence of the pesticide or its metabolites in the GC profile, suggesting complete mineralization.…”
Section: Discussionmentioning
confidence: 53%
“…No. 62 (Tu, 1976) result in g-PCCH as the first product of metabolism, whereas in Pseudomonas putida (Matsumura et al, 1976), two patterns of g-HCH degradation were observed, one being the dehydrochlorination pathway in which g-PCCH is formed. On the contrary, an anaerobic degrader such as Clostridium sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations